Quasi-Elastic Neutron Scattering Studies on Hydration Water in Phospholipid Membranes - Yamada, Takeshi; Seto, Hideki (Frontiers in Chemistry, 2020)
The dynamical behavior of hydration water at phospholipid membrane has been investigated to understand the relationship between water and biological molecules with various experimental techniques. Quasi-elastic neutron scattering (QENS) is an effective method for this purpose because the dynamical behavior of water molecules and that of lipid molecules could be identified by using selective deuteration. In addition, the measurable ranges from the 10^{-12} to 10^{-9} s time scale and the 10^{-2} to 10^1 nanometer length scale are suitable to investigate the slowing down of water molecules due to the interaction with lipid membranes. In this mini-review, QENS experiments on the dynamical behavior of hydration water molecules in neighboring phospholipid membranes are summarized.